Corporate information systems management : - Applegate, Lynda M. (Irwin/McGraw-Hill, 1999)
Corporate Information Strategy and Management: Text and Cases 5/e by Applegate, Austin and McFarlan is written for students and managers who desire an overview of contemporary information systems technology (IT) management. It explains the relevant issues of effective management of information services activities and highlights the areas of greatest potential application of the technology. No assumptions are made concerning the reader's experience with IT, but it is assumed that the reader has some course work or work experience in administration or management. This text is comprised of an extensive collection of Harvard Business cases devoted to Information Technology.